2008
DOI: 10.1007/s10562-008-9791-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Osmium(VIII) Catalysed Oxidation of Sulfanilic Acid by Hexacyanoferrate (III) in Alkaline Medium

Abstract: The kinetics of osmium(VIII) catalyzed oxidation of sulfanilic acid (p-aminobenzenesulfonic acid) by hexacyanoferrate(III) (HCF(III)) in alkaline medium was studied spectrophotometrically. The reaction showed first order kinetics in hexacyanoferrate(III) and osmium concentrations and an order of less than unity in sulfanilic acid (SAA) and alkali concentrations. The rate of reaction increased with increase in alkali concentration. Increasing ionic strength and dielectric constant of the medium increased the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…k 2 K 2 was evaluated from the intercept to be 10.1 ± 1.0 × 10 8 , 11.6 ± 1.0 × 10 8 and 12.9 ± 2.0 × 10 8 dm 6 mol −2 s −1 at 40, 45 and 50°C, respectively, and I = 0.5 mol dm −3 . These values of K 1 and k 2 K 2 were further substituted in rate equation (11), with the values of k (obs) and k (cal) being in close agreement despite the system being complex in nature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…k 2 K 2 was evaluated from the intercept to be 10.1 ± 1.0 × 10 8 , 11.6 ± 1.0 × 10 8 and 12.9 ± 2.0 × 10 8 dm 6 mol −2 s −1 at 40, 45 and 50°C, respectively, and I = 0.5 mol dm −3 . These values of K 1 and k 2 K 2 were further substituted in rate equation (11), with the values of k (obs) and k (cal) being in close agreement despite the system being complex in nature.…”
Section: Discussionmentioning
confidence: 97%
“…However, reactions in alkaline medium [1][2][3][4][5][6][7][8] are not fast probably due to the reduced oxidation potential of the [Fe(CN) 6 ] 3− /[Fe(CN) 6 ] 4− redox couple. 9 It is for this reason that a large number of transition metal ions such as Os(VIII), [10][11][12][13] Ru(III), [14][15][16][17] Ru(VI), 18 Ru(IV), 19 Rh(III), 20 Ir(III), 21 Ru(VIII) 22 and Pd(II) 23,24 have been employed as catalysts in alkaline medium. A large number of Os(VIII)-catalysed oxidations of both organic [25][26][27][28][29][30] and inorganic [31][32][33] compounds with hexacyanoferrate(III) in alkaline media have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ionic strength on the rate can be understood essentially on the basis of ionic species involved in the rate limiting step [20]. The change in the solvent composition by varying the methanol content in methanol-water affects the reaction rate the effect of varying solvent composition on the reaction kinetics has been described in several publications [21,22]. Amis has shown that a plot of log k C versus 1/D is linear with a negative slope for a reaction between a negative ion and a dipole or two dipoles, and with a positive slope for a positive ion-dipole interaction [23].…”
Section: Discussionmentioning
confidence: 99%
“…The progress of the reaction was followed by measuring absorbance of Fe[(CN) 6 ] 3− in the reaction mixture at 420 nm in a 1-cm cell placed in the cell compartment of an Varian carry 50 Bio UV–Vis spectrophotometer. Application of Beer’s law under the reaction conditions had been verified at 420 nm ( ε  = 1,070 ± 10 dm 3  mol −1  cm −1 ) [27]. In uncatalyzed and catalyzed cases, the kinetics was followed to more than 90 % completion of the reaction and good first-order kinetics were observed.…”
Section: Methodsmentioning
confidence: 99%